Analysis of Vaginal Candidiasis Prevalence among Bangladeshi women in relation to menstrual hygiene and other risk factors: A cross-sectional study - Gomes, Bristy Gloria (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.